Jurassic Park [videorecording (DVD)] - Spielberg, Steven, 1946-; Crichton, Michael, 1942-2008; Neill, Sam; Dern, Laura; Goldblum, Jeff, 1952- (Universal Studios Home Entertainment, 2012)
This epic film is sheer movie-making magic that was 65 million years in the making. Jurassic Park takes you to an amazing theme park on a remote island where dinosaurs once again roam the earth and five people must battle to survive among the prehistoric predators.